Flexoelectric MEMS: towards an electromechanical strain diode - Bhaskar, U K; Banerjee, N; Abdollahi, A; Solanas, E; Rijnders, G; Catalan, G (Nanoscale, 2016)
Piezoelectricity and flexoelectricity are two independent but not incompatible forms of electromechanical response exhibited by nanoscale ferroelectrics. Here, we show that flexoelectricity can either enhance or suppress the piezoelectric response of the cantilever depending on the ferroelectric polarity and lead to a diode-like asymmetric (two-state) electromechanical response.